Gendering modernism a historical reappraisal of the canon - Bucur-Deckard, Maria 1968- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"A critical narrative of how gender norms and the modernist movement shaped one another in the early 20th century, using vivid case studies"--Provided by publisher.